PROCESS AND UPDATES ON KAHAWOTINO LAMBU TRADITION ON MUNA TRIBE IN SOUTHEAST SULAWESI - Tiarnita Maria Siregar; Naufal Nasution; Hamida Mutia Sari Hutagalung (Adisam Publisher, 2023)
This study investigated the existence and transmission of the Kahawotino Lambu tradition in the Muna ethnic group of Southeast Sulawesi. The study found that the Kahawotino Lambu tradition is a tradition of entering a new house that is carried out by the Muna ethnic group. The tradition is considered by the Muna ethnic group as a way to express gratitude to God for His mercy and sustenance.The study also found that the younger generation is less likely to follow the kLambu tradition than the older generation.The younger generation is more likely to follow the development of the times and the advancement of science and technology.The study concluded that the Kahawotino Lambu tradition is facing a decline in existence. This is due to a number of factors, including the changing beliefs of the younger generation and the influence of modern culture.